2019
DOI: 10.1177/0284185119836232
|View full text |Cite
|
Sign up to set email alerts
|

Do radiologists detect chronic thromboembolic disease on computed tomography?

Abstract: Background: Acute pulmonary embolism (APE) is a potentially severe medical condition with blood clots obstructing the pulmonary arterial vasculature. In most cases the APE resolves without any sequelae after anticoagulation therapy. In some patients, however, the emboli do not resolve upon treatment and the remnants cause increased vascular resistance, a condition known as chronic thromboembolic pulmonary hypertension (CTEPH). Both APE and CTEPH have a non-specific clinical presentation and imaging is an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 70 publications
(141 reference statements)
0
23
2
1
Order By: Relevance
“…Also, radiologists need to be trained and experienced in assessing imaging findings of CTEPH, as demonstrated in a study assessing original CT reports from patients with confirmed CTEPH diagnosis referred to an expert PEA center (n = 35). 32 Although most cases were visible with CT in this study, only 26% of reports identified CTEPH or signs of CTEPH, leading to a falsely low sensitivity for CT. In patients with CTEPH, the use of electrocardiogram (ECG)-synchronized techniques in ECG-gated CT can provide detailed visualization of segmental and subsegmental vessels, lung parenchyma, and RV myocardial size and morphology, especially in the left lower lobe.…”
Section: Insert Figure Herecontrasting
confidence: 52%
“…Also, radiologists need to be trained and experienced in assessing imaging findings of CTEPH, as demonstrated in a study assessing original CT reports from patients with confirmed CTEPH diagnosis referred to an expert PEA center (n = 35). 32 Although most cases were visible with CT in this study, only 26% of reports identified CTEPH or signs of CTEPH, leading to a falsely low sensitivity for CT. In patients with CTEPH, the use of electrocardiogram (ECG)-synchronized techniques in ECG-gated CT can provide detailed visualization of segmental and subsegmental vessels, lung parenchyma, and RV myocardial size and morphology, especially in the left lower lobe.…”
Section: Insert Figure Herecontrasting
confidence: 52%
“…Although a ventilation/perfusion scan remains the recommended imaging modality for screening for CTEPH, CTPA is routinely used to confirm the presence of chronic pulmonary emboli in patients with an abnormal ventilation/perfusion scan [2]. In addition, although its role is underreported, CTPA may also identify patients with CTEPH at the time of acute pulmonary embolism where CTEPH was unsuspected [13,14]. Compared with conventional angiography, CTPA is noninvasive, faster to perform, generates lower radiation and is less operator dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results to ours were found in a previous study retrospectively evaluating CTPA reports in which (signs of] CTEPH were mentioned in only 9 of 35 (26%] reports. [7] Of note, in daily practice, CTPAs are frequently assessed by Abbreviations: PE, pulmonary embolism; CTEPH, chronic thromboembolic pulmonary hypertension; VTE, venous thromboembolism; COPD, chronic obstructive pulmonary disease. radiologists without specific expertise in thoracic radiology since patients with suspected acute PE often present out of office hours.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Confirmation of prevalent findings suggestive of CTEPH have been confirmed by recent studies, although it has also been suggested that radiologists rarely report these signs. [1,[5][6][7][8] More detailed assessment of index CTPAs may therefore lead to earlier identification of patients with (high risk of developing) CTEPH, which is associated with better prognosis. [9) In the InShape III study, three expert chest radiologists scored signs of chronic thrombi and pulmonary hypertension on CTPA scans performed for suspected acute PE in 50 PE patients who were subsequently diagnosed with CTEPH during follow-up ('cases'), and in 50 PE patients in whom sequential echocardiograms performed >2 years after the acute PE diagnosis had not shown any signs of pulmonary hypertension ('controls').…”
Section: Introductionmentioning
confidence: 99%